Porcine neonates failing vitality score: physio-metabolic profile and latency to the first teat contact - M.E. Trujillo-Ortega; D. Mota-Rojas; O. Juárez; D. Villanueva-García; P. Roldan-Santiago; M. Becerril-Herrera; R. Hernández-González; P. Mora-Medina; M. Alonso-Spilsbury; A.M. Rosales; R. Martínez-Rodríguez; R. Ramírez-Necoechea (Czech Journal of Animal Science, 2011)
The objective of this study was to compare the metabolic and electrolytic profile as well as the morphological appearance of the umbilical cord and newly born piglets' weight that failed the vitality test scale compared to those who passed. Newborn piglets were divided into three groups according to the vitality with a modified Apgar score at birth: Group 1, failing with a score < 5 (G1: n = 218), Group 2 had a score of 6 to 7 (G2: n = 439) and Group 3 had scores > 8 (G3: n = 464). Results showed significant differences among groups (P < 0.05) in the physio-metabolic pH, PCO2, PO2, Na+, Ca2+, glucose, lactate and bicarbonate values. Regarding weight, temperature and latency to connect the maternal teat, there were also significant differences (P < 0.05) among groups; it took 23.38 min for G3 while neonatal piglets from G1 took 30 min longer (P < 0.05) to make the first teat contact. The neonates from the latter group had a higher percentage (75.68%) of broken umbilical cords, with higher birth weight (+200 g, P < 0.05), showed higher than normal blood glucose concentrations, and had lower body temperature at birth (-0.7°C, P < 0.05) and PO2 in comparison with the other groups of neonates that passed the vitality score. A novel point of this study is the profile characterization of piglets that failed and passed the vitality score; we expect that the data provided may be applicable as reference values of metabolic and electrolyte blood profiles in newborn piglets according to their vitality. In conclusion, this study demonstrates that low vitality newborn piglets had clearly undergone through perinatal asphyxia. Potential indicators increasing this condition are: high birth weight, low body temperature, vitality score ≤ 5, and the presence of the broken umbilical cord at birth.